An Overview of Distributed Ledger Technology and its Applications - Masood, Faraz; Faridi, Arman Rasool (International Journal of Computer Sciences and Engineering, 2025)
With the release of Bitcoin in 2008, the technology behind it, Blockchain which is based on Distributed Ledger Technology is getting popular day by day and there is continuous development and improvement in Distributed Ledger Technologies. In this paper we have not restricted ourselves to Blockchain and we have introduced some popular Distributed Ledger Technologies, a little bit about their technical implementation and areas where it can be used to make workflow easier, efficient and transparent. A number of publications and organizations websites and blogs have been analyzed to find the best practical applications of Distributed Ledger Technologies and various companies working on its implementation.